Dominasi Id Tokoh dalam Novel Anak Bajang Mengayun Bulan: Kajian Psikoanalisis Freud: The Dominance of the Character's Id in the Novel Anak Bajang Mengayun Bulan: A Study of Freud's Psychoanalysis - Aulia, Aulia (JBSI: Jurnal Bahasa dan Sastra Indonesia, 2025)
Sindhunata's novel Anak Bajang Mengayun Bulan depicts complex emotional and psychological experiences through a symbolic storyline rooted in Javanese culture. This work presents characters who experience inner conflicts, such as Sukrosono, Sumantri, Dewi Sokawati, and Begawan Swandagni, who struggle with desire, rejection, and longing. These narrative layers provide a rich foundation for analyzing how human instinctive drives shape behavior, identity, and emotional development in literary structures. This study uses a qualitative descriptive method with a literary psychology approach. The analysis is based on Sigmund Freud's psychoanalytic theory, mainly focusing on the function and dominance of the id. Data were obtained through close reading techniques, character behavior and dialogue identification, and interpretation of symbolic elements that represent the work of the id in the narrative. The study results show that the id plays a central role in driving the actions and emotional responses of the characters. The id drives Sukrosono's longing for motherly love, Sumantri's ambition for power, and Swandagni's surrender to pleasure. Even Dewi Sokawati's maternal instinct reflects deep emotional impulses. This novel reflects universal psychological conflicts through the dominance of the id. This study confirms that traditional Indonesian literature, primarily through symbolic and mythological narratives, can effectively depict fundamental human struggles. This study also supports the integration of psychoanalytic perspectives in literary studies to reveal deeper emotional and psychological dimensions in fictional texts.